2010
DOI: 10.3748/wjg.v16.i20.2458
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic liver abscess: Differences in etiology and treatment in Southeast Asia and Central Europe

Abstract: Knowledge of etiology and timely treatment of underlying causes, when possible, play an important role in the successful therapy of patients with pyogenic liver abscess (PLA). Recent publications from Central Europe and Southeast Asia hint at considerable differences in etiology. In this article, we aim to elaborate these differences and their therapeutic implications. Apart from some special types of PLA that are comparable in Southeast Asia and Central Europe (such as posttraumatic or postprocedural PLA), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 53 publications
2
52
0
2
Order By: Relevance
“…For instance, the pathogenic distribution of PLA is subtly different between Asia and Europe. 1 The role of co-morbid diabetes mellitus in PLA has interesting controversies, as discovered by studies around the world. 2e4 Present evidence indicates a noticeable prevalence of PLA among the population in eastern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the pathogenic distribution of PLA is subtly different between Asia and Europe. 1 The role of co-morbid diabetes mellitus in PLA has interesting controversies, as discovered by studies around the world. 2e4 Present evidence indicates a noticeable prevalence of PLA among the population in eastern Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anaerobion infection may occur, so anti-anaerobic agents should be applied regularly. Treatment for E. histolytica may be conducted as follows: Drugs to eliminate E. histolytica in the inner organs are commonly used, assisted by radical treatment drugs for the treatment of intestinal amebiasis (3,14). Currently, metronidazole is the preferred antibiotic agent.…”
Section: Discussionmentioning
confidence: 99%
“…The image-guided percutaneous technique is a standard treatment of drainage [7]. Nevertheless, there remains a role for open or laparoscopic surgical intervention in the management of PLA with the documented indication as follows: no clinical response after four to seven days of percutaneous drainage; multiple, large, or loculated abscess; thick-walled abscess with viscous pus; and concomitant intra-abdominal surgical pathology [5,16,18,19]. Some authors have reported the efficacy and safety of emergent surgical drainage or resection [9,10,14,20,21].…”
Section: Discussionmentioning
confidence: 99%